Cynaropicrin: a comprehensive research review and therapeutic potential as an anti- hepatitis C virus agent - Elsebai, Mahmoud F.; Mocan, Andrei; Atanasov, Atanas G. (Frontiers in Pharmacology, 2016)
The different pharmacologic properties of plants-containing cynaropicrin, especially artichokes, have been known for many centuries. More recently, cynaropicrin exhibited a potential activity against all genotypes of hepatitis C virus (HCV). Cynaropicrin has also shown a wide range of other pharmacologic properties such as anti-hyperlipidemic, anti-trypanosomal, anti-malarial, antifeedant, antispasmodic, anti-photoaging, and anti-tumor action, as well as activation of bitter sensory receptors, and anti-inflammatory properties (e.g., associated with the suppression of the key pro-inflammatory NF-κB pathway). These pharmacological effects are very supportive factors to its outstanding activity against HCV. Structurally, cynaropicrin might be considered as a potential drug candidate, since it has no violations for the rule of five and its water-solubility could allow formulation as therapeutic injections. Moreover, cynaropicrin is a small molecule that can be easily synthesized and as the major constituent of the edible plant artichoke, which has a history of safe dietary use. In summary, cynaropicrin is a promising bioactive natural product that, with minor hit-to-lead optimization, might be developed as a drug for HCV.